2022
DOI: 10.1590/1678-9865202235e210168
|View full text |Cite
|
Sign up to set email alerts
|

Can hospitalized patients adequately estimate their own food intake? A cross-sectional pilot study

Abstract: Objective To assess and identify factors linked to the accuracy of patients’ food intake estimations through a self-monitoring instrument filled in by the patient. Methods This cross-sectional study approached adult hospital patients subjected to regular or therapeutic diets. The actual food intake percentage was obtained by the ratio between the actual food intake and the amount of food served x 100. Patients had to complete a food chart including 9 circles representing plates of food in percentages (increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In total, twenty-three (15%) studies reported on validation of the reported method in comparison to another dietary assessment method in the acute setting (criterion validity) (Table 1) (24,28,30,36,41,44,53,54,72,82,87,94,98,117,122,123,125,135,140,147,153,160,174) . Estimated plate waste was the most common dietary assessment method which underwent validation, with fifteen (60%) of the twenty-three studies reporting on the validity of this method in comparison with a reference tool.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, twenty-three (15%) studies reported on validation of the reported method in comparison to another dietary assessment method in the acute setting (criterion validity) (Table 1) (24,28,30,36,41,44,53,54,72,82,87,94,98,117,122,123,125,135,140,147,153,160,174) . Estimated plate waste was the most common dietary assessment method which underwent validation, with fifteen (60%) of the twenty-three studies reporting on the validity of this method in comparison with a reference tool.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In total 15 (65%) studies reported using an objective (weighed) method as the reference method. However, intake was only weighed pre-and post-consumption in six (26%) studies with the other nine (39%) studies calculating intake on the basis of comparison of a standard portion to the weight of the food remaining after consumption (24,30,36,41,53,54,72,82,87,117,122,147,153,160,174) . The remaining eight (35%) studies assessed validity in comparison with reference methods reliant on estimation of consumption including estimated food records (n = 1, 4%), estimated plate waste (n = 5, 22%) or 24 h recalls (n = 2, 4%) (28,44,94,98,123,125,135,140) .…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations